2016
DOI: 10.3389/fpsyg.2016.00254
|View full text |Cite
|
Sign up to set email alerts
|

Training of Dental Professionals in Motivational Interviewing can Heighten Interdental Cleaning Self-Efficacy in Periodontal Patients

Abstract: Background: The success of periodontal therapy depends on the adherence of patients to professional recommendations. The aim of this study was to investigate the influence of a workshop in motivational interviewing (MI) on non-surgical periodontal treatment performed by dental students.Materials and Methods: In the experimental group patients with periodontitis were treated by students trained in MI, while in the control group patients were treated by students who had not been trained in MI. Clinical oral para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 35 publications
1
69
0
1
Order By: Relevance
“…One study showed a lower BOP in the experimental group compared to the non-MI control group (Jönsson et al, 2010 ). In two studies gingival inflammation decreased significantly higher in the experimental group than in the control group (Jönsson et al, 2009b ; Woelber et al, 2016 ). In two studies, plaque values showed a significantly higher reduction in the experimental group compared to the control group (Jönsson et al, 2009b , 2010 ).…”
Section: Resultsmentioning
confidence: 96%
“…One study showed a lower BOP in the experimental group compared to the non-MI control group (Jönsson et al, 2010 ). In two studies gingival inflammation decreased significantly higher in the experimental group than in the control group (Jönsson et al, 2009b ; Woelber et al, 2016 ). In two studies, plaque values showed a significantly higher reduction in the experimental group compared to the control group (Jönsson et al, 2009b , 2010 ).…”
Section: Resultsmentioning
confidence: 96%
“…Non-surgical periodontal treatment which includes healthcare education, instructions on proper brushing technique and the use of hygiene accessories, scaling and root planning have shown to provide good results in patients and improvement in their dental hygiene (Woelber et al, 2016). With only conservative periodontal treatment, there has been an improvement in patients' periodontal conditions, as well as a decrease in pocket depth and gain in clinical insertion (Türkoglu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who received two or more calls in a six-month period, not only had better medication adherence but also had a smaller likelihood of discontinuing their therapy [ 11 ]. Researchers found that dental students who used MI techniques had patients with increased self-efficacy of interdental cleanings compared to patients who received care from dental students who did not use MI techniques [ 12 ]. However, despite growing evidence, the exact strategy for training students on MI is still unclear.…”
Section: Introductionmentioning
confidence: 99%